Mechanisms of lithium action on generation of membrane potential oscillations of the Nitella cell - Radenovic, C.N.; Maksimov, G.V.; Grodzinskij, D.M. (Физиология растений и генетика, 2015)
The results on variable mechanisms of lithium action on generation of membrane potential (MP) oscillations in the Nitella cell are presented. Generating of several classes of oscillations, single and local impulses of the membrane potential depend strongly on the high lithium concentration in the nutrient solution (LiCl concentration 10 mM), when the cell membrane is strongly excited. The assertion is that oscillations of the MP are caused by the total oscillatory transport processes for Li.⁺, K.⁺, Na.⁺ and Cl⁻ in cell membrane. The hypothesis on mechanisms of oscillatory transport processes of ions (Li.⁺, Na.⁺, K.⁺ and Cl⁻) expressed over different classes of oscillations, single and local impulses of the membrane potential across the excitable membrane of the Nitella cell is proposed.